Benchmarks of Equality? School-Wide Positive Behavioral Interventions and Supports and the Discipline Gap. (January 2022) - Barclay, Christopher M.; Castillo, Jose; Kincaid, Don
In U.S. schools, Black and Latinx youth receive disciplinary action at rates greater than their White peers. In the context of systemic racism in the United States, proposed systemic solutions such as school-wide positive behavioral interventions and supports (SWPBIS) should be evaluated for their effectiveness in producing more equitable school discipline. In light of mixed evidence for a SWPBIS–equity relationship, this study examined the merits of five SWPBIS elements demonstrating promise in the literature or underexamined potential for reducing discipline rates and disparities for Black and Latinx students in a sample of 322 SWPBIS-implementing schools serving a total of 292, 490 students (19% Black, 28% Latinx) in a southeastern state. Multiple linear regression results indicated that higher fidelity to SWPBIS Classroom Systems was related to lower discipline risk for all students, including Black and Latinx students, but not more equitable discipline practices. Higher fidelity to SWPBIS Expectations was related to higher suspension risk among Black students, whereas higher levels of Recognition were related to more equitable suspension practices. No significant relationships were observed between Lessons and Data Analysis and disciplinary rates or equity. Implications for the research and practice of SWPBIS are discussed in the context of promoting more equitable and socially just discipline practices.